Trans-fistulary endoscopic drainage for post-bariatric abdominal collections communicating with the upper gastrointestinal tract - Bouchard, Simon; Eisendrath, Pierre; Toussaint, Emmanuel; Le Moine, Olivier; Lemmers, Arnaud; Arvanitakis, Marianna; Devière, Jacques (Endoscopy, 2016)
Background and study aims: Diverse endoscopic methods, such as placement of temporary self-expandable stents, have proven effective for the treatment of post-bariatric surgery leaks. However, some patients do not respond to the usual endoscopic treatment. This study tested the efficacy of an alternative treatment strategy based on trans-fistulary drainage with double-pigtail plastic stents. Patients and methods: We performed a retrospective analysis of patients with abdominal collections following bariatric surgery who were treated by trans-fistulary stenting between May 2007 and February 2015. Clinical success was defined as a sustained (> 4 months) clinical resolution (patient discharged from the hospital without antibiotics and able to resume a normal diet) and radiological response. Patient records, radiological images, and the hospital endoscopy database were reviewed. Results: A total of 33 patients (26 women/7 men, mean age 42 years [SD 11.2]) were included. Collections occurred after sleeve gastrectomy (n = 28) or after gastric bypass (n = 5). Fourteen patients were treated by trans-fistulary stenting as primary treatment, and 19 patients had undergone previous unsuccessful endoscopic treatment. No serious complication occurred during the drainage procedure. Clinical success was achieved in 26 patients (78.8 %). In two successfully treated patients, stents are still in place. Spontaneous stent migration occurred in 12 patients. In 12 patients, the stents were removed, either electively (n = 5) or because of complications (ulcerations n = 3, upper gastrointestinal symptoms n = 3, splenic hematoma n = 1). Conclusions: Trans-fistulary drainage of post-bariatric abdominal collections is safe and associated with high success rates. This technique can be considered in previously untreated patients, when a collection is not properly drained percutaneously, or after failure of other endoscopic treatments.